New ABC Chronic Kidney Disease Classification (2017)
Since 2002, KDOQI and KDIGO groups have searched the best way to assess, define and classify Chronic Kidney Disease (CKD) to facilitate their diagnosis and optimize treatment. Growing evidence in recent years has shown a strong link to albuminuric.